Allele and haplotype frequencies of 11 HLA loci in Koreans by next‐generation sequencing - Jung, Kiwook; Kim, Jisoo G.; Shin, Sue; Roh, Eun Youn; Hong, Yun Ji; Song, Eun Young (HLA, 2023)
Data on HLA genotype distribution, including DQA1 and DPA1, in the Korean population are limited. We aimed to investigate the allele and haplotype frequencies of 11 HLA loci in 339 Korean subjects using next‐generation sequencing (NGS)‐based HLA typing. A total of 339 samples from unrelated healthy subjects were genotyped for HLA‐A, ‐B, ‐C, ‐DRB1, ‐DRB3, ‐DRB4, ‐DRB5, ‐DQB1, ‐DQA1, ‐DPB1, and ‐DPA1 using two different NGS‐based HLA typing kits (166 tested using the NGSgo‐MX11‐3 kit [GenDx, Netherlands] and 173 by the AllType NGS 11 Loci Amplification kit [One Lambda, USA]). PyPop software was used to estimate allele and haplotype frequencies and linkage disequilibrium between the loci. Additionally, a principal component analysis was performed to compare the allele distribution of Koreans with that of other populations. A total of 214 HLA alleles (97 class I and 117 class II alleles) were assigned. The most frequent alleles for each locus were A*24:02:01 (24.78%), B*15:01:01 (10.18%), C*01:02:01 (18.44%), DRB1*04:05:01 (9.59%), DRB3*02:02:01 (13.72%), DRB4*01:03:01 (25.81%), DRB5*01:01:01 (9.0%), DQA1*01:02:01 (16.96%), DQB1*03:01:01 (14.31%), DPA1*01:03:01 (44.4%), and DPB1*05:01:01 (35.1%), respectively. The most frequent haplotypes were A*33:03:01‐C*03:02:02‐B*58:01:01 for HLA class I (5.01%) and DRB1*04:05:01‐DQA1*03:03:01‐DQB1*04:01:01‐DPA1*02:02:02‐DPB1*05:01:01 for HLA class II (6.23%). The total allelic ambiguities by NGS were estimated to be minimal and considerably decreased compared with those by Sanger sequencing. The Japanese population had the most similar allele distribution to Koreans, followed by the Chinese population. Frequency data of 11 HLA loci in Koreans can provide essential data for population genetics and disease association studies.